Differential clinical pharmacology of rolapitant in delayed chemotherapy-induced nausea and vomiting (CINV) - Rashad N; Abdel-Rahman O (Dove Medical Press, 2017)
Noha Rashad,1 Omar Abdel-Rahman2 1Medical Oncology Department, Maadi Armed Forces Hospital, 2Clinical Oncology Department, Faculty of Medicine, Ain Shams University, Cairo, Egypt Abstract: Rolapitant is a highly selective neurokinin-1 receptor antagonist, orally administered for a single dose of 180 mg before chemotherapy with granisetron D1, dexamethasone 8 mg BID on day 2–4. It has a unique pharmacological characteristic of a long plasma half-life (between 163 and 183 hours); this long half-life makes a single use sufficient to cover the delayed emesis risk period. No major drug–drug interactions between rolapitant and dexamethasone or other cytochrome P450 inducers or inhibitors were observed. The clinical efficacy of rolapitant was studied in two phase III trials in highly emetogenic chemotherapy and in one clinical trial in moderately emetogenic chemotherapy. The primary endpoint was the proportion of patients achieving a complete response (defined as no emesis or use of rescue medication) in the delayed phase (>24–120 hours after chemotherapy). In comparison to granisetron (10 µg/kg intravenously) and dexamethasone (20 mg orally) on day 1, and dexamethasone (8 mg orally) twice daily on days 2–4 and placebo, rolapitant showed superior efficacy in the control of delayed and overall emesis. This review aims at revising the pharmacological characteristics of rolapitant, offering an updated review of the available clinical efficacy and safety data of rolapitant in different clinical settings, highlighting the place of rolapitant in the management of chemotherapy-induced nausea and vomiting (CINV) among currently available guidelines, and exploring the future directions of CINV management. Keywords: nausea, vomiting, chemotherapy, rolapitant, CINV